MODEL ZONASI KETAHANAN PANGAN DENGAN PENDEKATAN PARTISIPATIF DI WILAYAH SOLORAYA - Ana Hardiana; Malik Cahyadin; Evi Gravitiani (Diponegoro University, 2012)
Purposes of this research are: a) to identify spatial policy (mapping) of agriculture in the Soloraya region, b) to analyze the correspondence between spatial policy and implementation in the field of agricultural, and c) to analyze agricultural mapping to support food security and safety with participation approach. Research methods are descriptive analysis and mapping. Conclusions of this research are: 1) agricultural policy in the Soloraya region is reflected in RTRWD and RPJMD. RTRWD conduct and guide the agricultural mapping while RPJMD regulate and determine the direction of agricultural development, 2) correspondence between policy and implementation of agriculture in each region in Soloraya are reflected in form of area and and food production conditions. Each region has tried to make adjustments through many stages according to RTRWD and RPJMD, and 3) a mapping model of food security in each region is determined based on several assumptions. The end result of this research is a mapping of food producers in each sub-district for approximately two years.